182 Pediatric Craniotomies: Incidence, Predictors, and Costs for a Tristate Analysis With 1-Year Readmission Follow-up. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Iorgulescu, Bryan; Souweidane, Mark M.; Greenfield, Jeffrey P.; Parsa, Andrew T.
Abstract: INTRODUCTION: The relative paucity of pediatric neurosurgical conditions necessitates tremendous population sizes in order to robustly assess the quality and outcomes of present care. Although intrinsically limited by their coarse resolution, national databases are becoming increasingly powerful and validated to the point of enabling the regimented analysis of outcomes and their predictors. METHODS: Statewide inpatient datasets comprising 100% of hospital discharges in the 3 most populous states with longitudinal identifiers (California, Florida, and New York), which track patients across multiple admissions, institutions, and years, were examined for 2006 to 2010. Algorithms constructed from The International Classification of Diseases, Ninth Revision codes and validated with chart review were used to identify all-cause craniotomies and craniectomies, prospectively-designated predictors and outcomes. Initial operations in 2006 or 2010 were excluded to ensure at least 1 year of follow-up, age >21, and prior craniotomy were also excluded. Primary outcomes, secondary outcomes, and predictors (including reason for operation, neurological sequelae, hospital volume, Charlson comorbidity index, and demographics) were analyzed with logistic regression. RESULTS: California, Florida, and New York together comprise 24% of the US population. There were a total of 11, 135 all-cause craniotomies for 10, 159 kids over the 5-year sample, with 6027 patients remaining after exclusion, at a median inflation-adjusted admission cost of $28 542 (interquartile range [IQR]: 16 498-54 623). Postoperatively, 9% of patients were readmitted for re-operation (median time to readmission: 139 days, IQR: 42-371) and 34% were readmitted with new-onset primary outcomes including convulsions (8%; median 174 days, IQR: 50-366), hydrocephalus (6%; median 105 days, IQR: 36-296), and hemorrhage (4%; median 84 days, IQR: 26-239). Additionally, there were readmissions with sepsis (4%; median 148 days, IQR: 59-301), meningitis (3%; median 42 days, IQR: 14-312), and VFib (0.3%; median 272 days, IQR: 112-549). Notably, 4% of children died during the initial admission, at a median of 4 days after craniotomy (IQR: 2-9), but only a 0.3% mortality on the day of surgery. CONCLUSION: Children were most frequently readmitted for outcomes associated with neurological condition and comorbidities at presentation. These findings reinforce the need for extended vigilance and careful follow-up of children, in which many neurosurgical sequelae present beyond the traditional postoperative periods of 30 to 180 days.